Tailoring a Near‐Infrared Macrocyclization Scaffold Allows the Control of In Situ Self‐Assembly for Photoacoustic/PET Bimodal Imaging. (16th February 2022) - Wang, Yuqi; Bai, He; Miao, Yinxing; Weng, Jianhui; Huang, Zheng; Fu, Jiayu; Zhang, Yan; Lin, Jianguo; Ye, Deju
Abstract: Enzyme‐triggered macrocyclization and in situ self‐assembly of small molecules into nanoparticles has shown promise to design activatable probes for molecular imaging. However, controlling macrocyclization and self‐assembly to concurrently augment positron emission tomography (PET) and photoacoustic (PA) signals for bimodality imaging is challenging. Herein, we report the engineering of a triazole‐IR780 fluorophore as a versatile macrocyclization scaffold for controlling in situ self‐assembly and design a caspase‐3‐activatable PA/PET bimodal probe ([ 18 F]‐IR780‐1 ) for in vivo imaging of tumor apoptosis. By leveraging the high‐sensitivity whole‐body imaging signals offered by PET with the high‐resolution imaging signals offered by PA, [ 18 F]‐IR780‐1 can provide a promising tool for the early evaluation of antitumor efficacy, helpful for optimizing the therapeutic protocol for patients. This scaffold may be adopted to design other activatable bimodal probes for in vivo imaging. Abstract : A near‐infrared triazole‐IR780 fluorophore was tailored as a PAI‐active macrocyclization scaffold for controlling macrocyclization and in situ self‐assembly, which enabled the development of a caspase‐3‐activatable PET/PAI bimodal probe [ 18 F]‐IR780‐1 for noninvasive imaging of drug‐induced tumor apoptosis in vivo, with potential for the early monitoring of tumor response to chemotherapy.